2019
DOI: 10.3177/jnsv.65.38
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Functional Constipation and Dietary Habits in School-Age Japanese Children

Abstract: Functional constipation negatively affects school-related quality of life for children and adolescents. We investigated the association between functional constipation, defined according to the Rome criteria version III, and dietary habits. The subjects of this cross-sectional study were 1,140 5th graders and 1,054 8th graders attending schools in Shunan City, Japan in 2012. Functional constipation was defined as having two or more symptoms of constipation. Dietary habits were assessed using a brief questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
(68 reference statements)
0
7
0
3
Order By: Relevance
“…da fibra alimentar ingerida foi obtida de produtos ultraprocessados [16]. Um estudo realizado com crianças japonesas encontrou o consumo médio de fibra alimentar de 11,3 g/dia [17].…”
Section: Discussionunclassified
“…da fibra alimentar ingerida foi obtida de produtos ultraprocessados [16]. Um estudo realizado com crianças japonesas encontrou o consumo médio de fibra alimentar de 11,3 g/dia [17].…”
Section: Discussionunclassified
“…Some scholars have found that food affects all aspects of body functions, and it can be used for good health or prevention of disease [13]. Consumption of functional foods alleviates constipation and its symptoms [14]. In view of the unique efficacy of L-arabinose in alleviating constipation, the effect of L-arabinose on constipation in experimental constipation mouse model was investigated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary intake is closely related with health outcomes in school-age children, which includes risks of cardiovascular, digestive, bone, and allergic diseases [1,2,3,4]. Dietary habits of macronutrient and food intake are known to be retained from childhood to adulthood [5,6,7], and unhealthy dietary habits are associated with cardiovascular risks in adults [8].…”
Section: Introductionmentioning
confidence: 99%